2020
DOI: 10.1016/j.ebr.2020.100388
|View full text |Cite
|
Sign up to set email alerts
|

Acquired epileptiform aphasia: 44 years after diagnosis

Abstract: We report a case of a 48-year-old woman who was diagnosed with Landau-Kleffner syndrome (LKS) at the age of 4 and reassessed by the same neurologist four decades later. While her seizures abated by the time she was 12 years old, she was left with chronic aphasia, despite receiving optimal care. Although she graduated from high school, started her own family, and was gainfully employed, she was vulnerable in situations that required clear communication. This case reflects successful management of an otherwise d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…According to a retrospective study of Caraballo et al, at the end of a mean follow-up of 12 years, only eight out of 29 LKS cases recovered their language completely, while 21 cases still showed language deficits of different degrees [162]. Patients with LKS could need life-long support due to persisting and potentially debilitating deficits of verbal communication [188]. In a retrospective study involving 11 children, four cases showed no language problems after adolescence, four cases had moderate language problems, and three cases presented a severe language impairment > 10 years after the diagnosis [189].…”
Section: Outcomementioning
confidence: 99%
“…According to a retrospective study of Caraballo et al, at the end of a mean follow-up of 12 years, only eight out of 29 LKS cases recovered their language completely, while 21 cases still showed language deficits of different degrees [162]. Patients with LKS could need life-long support due to persisting and potentially debilitating deficits of verbal communication [188]. In a retrospective study involving 11 children, four cases showed no language problems after adolescence, four cases had moderate language problems, and three cases presented a severe language impairment > 10 years after the diagnosis [189].…”
Section: Outcomementioning
confidence: 99%